THE INFLUENCE OF LEARNING MODEL, EMOTIONAL INTELLIGENCE, AND ITS INTERACTIONS ON RESPONSE AND MATHEMATICS LEARNING OUTCOMES OF GRAD VIII STUDENTS AT SMPN 3 IN MAKASSAR - Sirajuddin Sirajuddin (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2016)
The study aims at examining (i) the influence of learning model (discovery learning and cooperative learning of NHT type) on response and Mathematics learning outcomes of grade VIII students at SMPN 3 in Makassar, (ii) the influence of emotional intelligence on response and Mathematics learning outcomes of grade VIII students at SMPN 3 in Makassar, (iii) the influence of interactions between emotional intelligence and learning model (discovery learning and cooperative learning of NHT type) applied to grade VIII students at SMPN 3 in Makassar. The population of the study was grade VIII students at SMPN 3 in Makassar of academic year 2015/2016 which consisted of 9 homogenous classes with the total of 351 students. Two out of nine classes were chosen as the experiment  units as experiment class 1 and experiment class 2 taken by employing simple random sampling technique and obtained class VIII7 as the experiment class 1 and class VIII9 as the experiment class 2. Class VIII7 as the experiment class I applied discovery learning and class VIII9 as the experiment class 2 applied cooperative learning model of NHT type. The type of the study was quasi experiment which characterized by the treatment on the objects to be studied. Data were collected by employing observation sheet, questionnaire, test, and documentation study. Data were then analyzed by using MANOVA with IBM SPSS Amos version 20. The results of the study reveal that (i) there is influence of learning model (discovery  learning and cooperative  learning  of NHT type) on the response  and Mathematics learning outcomes of grade VIII students at SMPN 3 in Makassar, in this case the response  and Mathematics  learning outcomes of students who were taught by using discovery learning is higher than the ones taught by using cooperative learning model of NHT type, (ii) there is influence of emotional intelligence (high and low) on students' response and Mathematics learning outcomes of grade VIII students at SMPN 3 in Makassar, in this case the response and Mathematics learning outcomes of students who have high emotional intelligence is higher than the students who have  low emotional  intelligence,  and  (iii) there  is influence  of interactions between  learning  model  and  emotional  intelligence  on  students’ response  and Mathematics  learning  outcomes  of  grade  VIII  students  at  SMPN  3  in  Makassar.